ANALYSIS OF MORPHOFUNCTION CHARACTERISTICS OF GENERAL SECONDARY SCHOOL STUDENTS OF FERGANA CITY (Conferencea, 2023)
The article examines the practical application of the method of canonical values in determining the physical fitness of secondary school students of Fergana city , as well as the issues of determining the canonical value and canonical correlations between indicators.